Batch cycle time reduction analysis in a small vaccine development facility - Wilmes, Leigh (Kansas State University, 2022)
Batch cycle time is an important component of a vaccine development company. In a mature economy, pharmaceutical manufacturing companies aren’t coming up with new and novel ideas but being first to market and making sure that store shelves are stocked are the most important strategies for success. If a company has long batch cycle times this could delay them getting product to market and risk an increase in backorders. This research involves exploring sources of batch cycle time challenges at Trivax, a startup vaccine development company that, interestingly, enough started operations a couple of years before the Covid-19 pandemic. The study will analyze their data for vaccine production units and individual vaccines to identify the cause of the longer batch cycle days occurring in some of their production lines. It will also evaluate the effect of implementation of mitigation strategies the batch cycle days. Data was collected using the Tableau software program. Averages of batch cycle days were collected for vaccine production units for a series of months over two years. Further breaking down the data collecting to five individual vaccines within the lowest percent change vaccine unit from the year 2020 to 2021. The data collected shows that the vaccine units all have higher than theoretical batch cycle days and even with the implementation of mitigation strategies, continue to be high. Trivax identified two areas of focus for further research and have started that research to try and uncover the issues behind the high number of batch cycle days.
Keywords: Animal health; Pharmaceutical; Agribusiness; Efficiencies; Vaccine